Today's Sounds for Yesterday's Films
XI, 225 p.
Keywords: In recent years, there has been something of an explosion in the performance of live music to silent films. There is a wide range of films with live and new scores that run from the historically accurate orchestral scores to contemporary sounds by groups such as Pet Shop Boys or by experimental composers and gothic heavy metal bands. It is no exaggeration to claim that music constitutes a bridge between the old silent film and the modern audience; music is also a channel for non-scholarly audiences to gain an appreciation of silent films. Music has become a means both for musicians and audiences to understand this bygone film art anew. This book is the first of its kind in that it aims to bring together writings and interviews to delineate the culture of providing music for silent films. It not only has the character of a scholarly work but is also something of a manual in that it discusses how to make music for silent films.